United States and China on a collision course: The importance of domestic politics for the bilateral relationship - Hanns W. Maull; Angela Stanzel; Johannes Thimm (Stiftung Wissenschaft und Politik (SWP), 2023)
No other bilateral relationship has comparable significance for the future of the international order as that between the United States and the People's Republic of China.Domestic political and social structural factors have a significant influence on the conflict behaviour of the two states. These factors are contributing towards the deterioration of the bilateral relationship and making it crisis-prone. Vulnerabilities arise from the interdependencies between the two societies and economies. An awareness of this fact can provide an incentive for cooperation. Efforts made to avoid the risk of escalation can also promote cooperation. Both states are dependent on a functioning international order. However, this insight is all too easily overshadowed by the conflictual aspects of the bilateral relationship. This is the task - and at the same time an opportunity - for German and European policy, which should strengthen European participation in world governance to gain more weight and exert a moderating influence on China and America.
Keywords: 320; US; China; Russia; Ukraine war; Xi Jinping; Joe Biden; bilateral relationship; international order; Covid pandemic; CHIPS and Science Act; competition; industry; economic espionage; research and development; semiconductors